1998
DOI: 10.1021/ma981020c
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Syndiotactic Copolymers of Propene with 1-Butene

Abstract: The structural characterization of syndiotactic copolymers of propene with 1-butene, prepared with a single-center metallocene-based catalyst, is reported. The copolymers are crystalline in a whole range of comonomer composition. The increase of a and b axes of the unit cell from the values of syndiotactic polypropylene to those of syndiotactic poly(1-butene), with increasing content of 1-butene, indicates that the comonomeric units, propene or 1-butene, are included in the unit cells of both homopolymers. As-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(93 citation statements)
references
References 23 publications
(118 reference statements)
5
88
0
Order By: Relevance
“…Apparently, the characteristic crystalline peaks are present at the scattering angles 2θ = 12.18 ± 0.03 °, 15.93 ± 0.03 °, 20.64 0.11 ° and 24.56 0.04 °. By consulting all the publications dedicated to crystallographical studies of s‐PP,20–34 we strongly believe that the results shown in Fig 1 can be best described by the limit‐disordered form I26, 28, 30 (after the most recent nomenclature given by De Rosa et al 35), which has an orthorhombic unit cell with axes a = 14.5 Å, b = 5.6 Å and c = 7.4 Å and exhibits an antichiral packing of chains only along the a axis (see Fig 1B in ref 35). The space group proposed for this crystal modification was Pcaa 21.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the characteristic crystalline peaks are present at the scattering angles 2θ = 12.18 ± 0.03 °, 15.93 ± 0.03 °, 20.64 0.11 ° and 24.56 0.04 °. By consulting all the publications dedicated to crystallographical studies of s‐PP,20–34 we strongly believe that the results shown in Fig 1 can be best described by the limit‐disordered form I26, 28, 30 (after the most recent nomenclature given by De Rosa et al 35), which has an orthorhombic unit cell with axes a = 14.5 Å, b = 5.6 Å and c = 7.4 Å and exhibits an antichiral packing of chains only along the a axis (see Fig 1B in ref 35). The space group proposed for this crystal modification was Pcaa 21.…”
Section: Resultsmentioning
confidence: 99%
“…To date, four limit-ordered crystalline modifications of s-PP were proposed and described in the literature. [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] Of the four crystalline forms, only the molecular chain packing models of the limitordered form I 56 -59,64,66 and the limit-disordered form I 59,63,66 (after the most recent nomenclature given by De Rosa et al 70 ) are appropriate for characterizing s-PP samples that are crystallized under quiescent conditions from the melt state (or from solution).…”
Section: Dependence Of Subsequent Melting Endotherms On Crystallizatimentioning
confidence: 99%
“…Nevertheless, comonomers of some copolymers do cocrystallize. [15][16][17][18][19][20][21][22][23][24][25][26] For example, De Rosa et al 16 studied the cocrystallization behavior of propene and 1-butene. With increasing content of 1-butene, the increase of a and b axes from the values of s-PP to those of s-PB indicates that the comonomers (propene or 1-butene) are included in the unit cells.…”
Section: Introductionmentioning
confidence: 99%